Effect of Using Two Cryopreservation Methods on Viability and Fertility of Frozen Stallion Sperm - Maziero, Rosiara Rosaria Dias; Guaitolini, Carlos Renato de Freitas [UNESP]; Guasti, Priscilla Nascimento [UNESP]; Monteiro, Gabriel Augusto; Martin, Ian; Silva, Juliano Pianowski Marques da; Crespilho, André Maciel; Papa, Frederico Ozanam [UNESP] (Elsevier, 2019)
Studies involving different methods and techniques of cryopreservation and its interactions with the conception rates in artificial insemination (AI) programs are reported in the literature. This study evaluated the sperm kinetics, plasma membrane integrity, and fertility rates of mares inseminated with cryopreserved stallion semen subjected to different freezing methods. For this, four ejaculates from five stallions were collected and frozen in conventional (Styrofoam box) or automated system in Mini-Digitcool ZH 400. Seminal samples were evaluated after thawing for sperm motion parameters by CASA and plasma membrane integrity by epifluorescence microscopy. For the fertility trial, a cross-over model was performed using 100 cycles of 50 mares, which were inseminated by one the two freezing methods. No differences were observed for sperm motion parameters and plasma membrane integrity between groups (P >.05). The pregnancy rate using the conventional method was 56% (28/50) and did not differ (P =.5406) from the pregnancy rate (64%, 32/50) obtained using the automatized method. The use of semen from fertile stallions may not illustrate small differences in the two freezing methods evaluated. Conventional and automated freezing systems did not differ in the quality and viability of fertile stallion semen and conception rates, indicating that the two methodologies can be safely used in AI programs.
Keywords: Equine; Fertility; Freezing protocol; Freezing rate; Semen cryopreservation